Assessment of Environmental Radiation Levels in Anambra South Senatorial District, Anambra State, Nigeria - Vivian C. Ezemba; Chijioke M. Amakom; Chinyere P. Ononugbo; Gregory O. Avwiri; Romanus E. Ugwoke (Environmental Health Insights)
The environmental radiation levels in Anambra South Senatorial District were evaluated through in situ measurements using a well-calibrated nuclear radiation meter (Radalert-100TM). A Global Positioning System (GPS) was utilized to record the exact coordinates of the selected locations. A total of 170 sampling locations were surveyed across the district. The average exposure rate across the district was measured as 0.0123 ± 0.0003 mRh −1 . The overall average values for the absorbed dose rate (ADR), equivalent dose rate (EDR), annual effective dose equivalent (AEDE), and excess lifetime cancer risk (ELCR) were 106.35 ± 2.82 nGyh −1 , 1.03 ± 0.03, 0.131 ± 0.004 mSvy −1 , and 0.459 ± 0.003 × 10 −3 , respectively. The findings indicate that the average exposure rates in the district were within the international threshold of 0.013 mRh −1 established by the International Commission on Radiation Protection (ICRP), suggesting that the region is generally safe for human habitation. However, the calculated radiological hazard indices, particularly ADR and ELCR, exceeded the permissible limits of 84 nGyh −1 and 0.29 × 10 −3 , respectively. While these elevated values do not pose an immediate radiological health threat, continuous exposure over a lifetime may present a significant risk to the population.